THE STATE FATE IN POLIBUSINESSES - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2015)
There is a new tendency in overcoming the problems of the nation. It appears all the stake-holders in this (legislative and executive) have played their role well to cause a decreasing in public trust in them. The case of